Meningkatkan Potensi Lokal: Pemberdayaan Perempuan Melalui Pelatihan Sulaman Kapalo Samek di Nagari Simpuruik, Tanah Datar - Alfisha Putri; Alisa Sani Mardia; Belinda Yulianti; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to describe the implementation of kapalo samek embroidery training in Nagari Simpuruik as an effort to promote economic empowerment and preserve local culture. Based on interviews with village officials and women participating in the training, it was found that most participants had already acquired embroidery skills through self-taught methods prior to the training. They were accustomed to working on embroidery either based on custom orders or in cooperation with "fabric bosses" who provided pre-designed cloth and threads. Embroidery has become a productive activity in Jorong Sijangek, mainly practiced by housewives. Although the training was conducted smoothly, the main challenge was gathering participants due to their limited availability. The market potential for kapalo samek embroidery is significant, especially during cultural or ceremonial events, but a major obstacle lies in marketing capabilities, particularly in digital platforms. Therefore, the training also served as a medium to introduce basic marketing strategies for craft products. In addition to enhancing economic capacity, the activity encourages cultural preservation by regenerating embroidery skills among the younger generation. This embroidery training highlights the importance of local initiatives in safeguarding cultural heritage and improving community welfare.